Anti-inflammatory effect of bergamot leaves extract attenuates cardiac remodeling in obese rats by regulating the protein expression of the collagen/metalloproteinase axis - Taynara Aparecida Vieira; Juliana Silva Siqueira; Erika Tiemi Nakandakare-Maia; Nubia Alves Grandini; Marina Gaiato Monte; Giovanna Baron; Dijon Henrique Salomé de Campos; Giancarlo Aldini; Silmeia Garcia Zanati Bazan; Fabiane Valentini Francisqueti-Ferron; Lilian Cristina Pereira; Marina Politi Okoshi; et al. (PLoS ONE, 2025)
Inflammation is associated with the pathogenesis of obesity-related disorders, including cardiac remodeling. Bergamot is known for its promising anti-inflammatory effects. Thus, this study aimed to investigate the anti-inflammatory effect of bergamot leaves extract (BLE) in attenuating cardiac remodeling in obese rats through the regulation of protein expression of the collagen/metalloproteinase axis. Male Wistar rats were fed a control diet (C) or a high sugar-fat diet (HSF) for 20 weeks. After developing cardiac remodeling, the animals were again distributed into three groups to receive BLE (50 mg/kg/day) or placebo (water) via gavage for 10 weeks: C, HSF and HSF + BLE. The HSF group exhibited obesity (HSF 8.77 ± 2.64 vs C 3.09 ± 1.02, p = 0.007), dyslipidemia (HSF 94.4 ± 19.1 vs C 26.7 ± 5.2, p < 0.001), hypertension (HSF 141 ± 8 vs C 120 ± 4, p = 0.001), insulin resistance (HSF 6.91 ± 1.38 vs C 2.47 ± 1.01, p < 0.001), cardiac remodeling and dysfunction, cardiac inflammation, decreased metalloproteinase-2 (MMP-2) (HSF 0.43 ± 0.09 vs C 0.71 ± 0.07, p = 0.009) and increased type III collagen (HSF 1.32 ± 0.27 vs C 1.00 ± 0.18, p = 0.038). In contrast, BLE was effective in improving dyslipidemia (HSF + BLE 55.2 ± 9.7 vs HSF 94.4 ± 19.1, p < 0.001), insulin resistance (HSF + BLE 3.79 ± 0.76 vs HSF 6.91 ± 1.38, p < 0.001), cardiac remodeling and function, as well as inflammation, MMP-2 (HSF + BLE 0.84 ± 0.22 vs HSF 0.43 ± 0.09, p < 0.001) and type III collagen (HSF + BLE 0.68 ± 0.11 vs HSF 1.32 ± 0.27, p < 0.001) in the HSF group. Therefore, the anti-inflammatory effect of BLE improved cardiac remodeling in obese rats through the regulation of protein expression of the collagen/metalloproteinase axis.